Efecto de Seis Tipos de Sustratos y Tres Dosis de Ãcido a Naftalenacético en la Propagación Vegetativa de Mortiño (Vaccinium floribundum Kunth) - Silva, Vilma Fernanda Noboa (European Scientific Journal, ESJ, 2019)
The mortiÃ±o (Vaccinium floribundum Kunth) is a wild shrub still in the process of domestication in the country whose development is slow, and it requires more in-depth studies. This is a plant with social, cultural, ecological, productive and commercial value, being one of the few alternatives to improve the sustainability of the pÃ¡ramos in Ecuador. This paper focuses on testing six substrates and three doses of Î±-naphthaleneacetic acid in order to establish a vegetative propagation protocol. The experimental design applied is randomized complete blocks (BCA) with combinatorial arrangement 6 x 3 with 3 repetitions. The evaluations were carried out at 90, 120, and 150 days using the Tukey test at 5%. Here, the following parameter was recorded: percentage of capture, number of shoots per stake, and length of shoots. In the evaluations made, the T13 treatment (50% straw + 50% natural growth soil of the species, with a high dose of Î±-naphthaleneacetic acid ANA) was better in terms of percentage of shoot and number of shoots per stake (86.67% and 2.67) (buds / stake). For the length of shoots, the best result with 1.2 cm was the T1 treatment (100% natural growth soil with high dose of auxin). However, these results confirm that the species reacts favorably in soils of natural development. In combination with a means of aeration (pÃ¡ramo straw), the result is better. The high dose of synthetic auxin ANA has a significant effect on the development of the plant, even in cases where the natural soil of the growth of the species was not present. El mortiÃ±o (Vaccinium floribundum Kunth) es un arbusto silvestre aÃºn en proceso de domesticaciÃ³n en el paÃs cuyo desarrollo es lento y requiere de estudios mÃ¡s profundos. Esta es una planta con valor social, cultural, ecolÃ³gico, productivo y comercial, siendo una de las pocas alternativas para mejorar la sostenibilidad de los pÃ¡ramos en el Ecuador. El presente estudio estuvo dirigido a probar seis sustratos y tres dosis de Ã¡cido Î± naftalenacÃ©tico con el fin de establecer un protocolo de propagaciÃ³n vegetativa. El diseÃ±o experimental aplicado es el de bloques completos al azar (BCA) con arreglo combinatorio 6 x 3 con 3 repeticiones. Las evaluaciones fueron realizadas a los 90, 120 y 150 dÃas utilizando la prueba de Tukey al 5%, donde se registrÃ³: porcentaje de prendimiento, nÃºmero de brotes por estaca y longitud de brotes. En las evaluaciones realizadas el tratamiento T13 (50% paja + 50% tierra de crecimiento natural de la especie, con dosis alta de Ã¡cido Î± naftalenacÃ©tico A.N.A) fue mejor en cuanto a porcentaje de prendimiento y nÃºmero de brotes por estaca (86.67% y 2.67 brotes/estaca) y en longitud de brotes el que mejor resultÃ³ con 1.2 cm fue el tratamiento T1 (100% tierra de crecimiento natural con dosis alta de auxina), estos resultados confirman que la especie reacciona favorablemente en suelos de desarrollo natural y que en combinaciÃ³n con un medio de aireaciÃ³n (paja de pÃ¡ramo) el resultado es mejor. La dosis alta de auxina sintÃ©tica A.N.A incidiÃ³ para un mejor desarrollo de la planta, incluso en aquellos tratamientos donde la tierra natural de crecimiento de la especie no estuvo presente.